PANIBi2S3 nano composite material as well as preparation method and application thereof

The polyaniline-coated bismuth sulfide nanocomposite solves the problems of low radioactive iodine adsorption capacity and high cost in the existing technology, and achieves a more efficient iodine adsorption effect.

CN119327432AActive Publication Date: 2025-01-21NANJING UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411547831.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-21
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The prior art has problems with low adsorption capacity, high cost and toxicity in capturing and preserving radioactive iodine, especially the poor performance of activated carbon and silver exchange zeolite in practical applications.

Method used

A nanocomposite material of bismuth sulfide (Bi2S3) coated with polyaniline (PANI) is used. Through the preparation method, bismuth sulfide and chloroform are mixed, and aniline and acidic ammonium persulfate solution are added to form a nanocomposite material to improve the iodine adsorption capacity.

Benefits of technology

Achieving better iodine adsorption capacity, polyaniline not only improves the physical adsorption capacity, but also helps the adsorbent to be weakly alkaline, promotes the adsorption of iodine by bismuth sulfide, and promotes charge transfer through high conductivity, reducing the interaction between bismuth sulfide. of gathering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327432A_ABST
    Figure CN119327432A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adsorbents, and discloses a PANIBi2S3 nano composite material as well as a preparation method and application thereof, and the composite material is polyaniline coated bismuth sulfide; the bismuth sulfide is in the shape of a nanoflower. The nano composite material obtained by the invention has better iodine adsorption capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adsorbents, and in particular to a PANI Bi2S3 nanocomposite material and a preparation method and application thereof. Background Art

[0002] Since the beginning of the new century, in order to cope with energy shortages and environmental pollution, nuclear power has attracted widespread attention for its safety, efficiency, and economy. However, the nuclear power generation process inevitably produces a large amount of radioactive pollutants, posing a serious threat to human health and the ecosystem. Among them, radioactive iodine ( 129 I and 131 I) has attracted much attention due to its high environmental mobility and toxicity. 129 I and 131 I is the main isotope of radioactive iodine. 129 The half-life of I is 1.57×10 7 It is extremely volatile and once released, it will cause almost permanent damage to the environment and human health. 131 I has a relatively short half-life (8.02 days), but due to its high specific activity and high radioactivity, 131 The relative danger of I is much higher than that of other radionuclides. Therefore, timely and effective capture and preservation of radioactive iodine has become an urgent issue.

[0003] At present, the methods for removing radioactive iodine are mainly solution washing and solid adsorption. Solid adsorption is more popular in capturing radioactive iodine due to its high efficiency, low cost and simple operation. So far, different types of adsorbents have been successfully developed, including activated carbon, silver-exchanged zeolite (AgZ), aerogel, layered double hydroxide (LDH), porous organic polymer (POP), covalent organic framework (COF) and metal organic framework (MOF). Among them, activated carbon and silver-exchanged zeolite have been widely used in industrial applications, but due to its shortcomings such as low autoignition temperature, low adsorption capacity and susceptibility to external interference, activated carbon is not the best choice for capturing radioactive iodine in practical applications. Although silver-exchanged zeolite can react with iodine to produce AgI precipitate, the high cost and toxicity of silver further limit its application in practice.

[0004] Recently, bismuth-based materials are considered as alternatives to silver-based materials. Bismuth-based materials are widely used in industrial applications due to their non-toxicity, low cost and chemical stability, ability to process radioactive iodine at higher temperatures, and the formation of thermodynamically stable compounds BiI3 or BiOI. Bi2S3 is a simple and non-toxic metal sulfide that has been widely used in catalysis, battery adsorption and other fields. Some researchers have also used it to adsorb iodine, but its adsorption capacity cannot be further improved at present. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a PANIBi2S3 nanocomposite material and a preparation method and application thereof. The nanocomposite material obtained by the present invention has good iodine adsorption capacity.

[0006] The invention provides a PANI Bi2S3 nanocomposite material, wherein the composite material is polyaniline (PANI) coated with bismuth sulfide (Bi2S3).

[0007] Furthermore, the morphology of the bismuth sulfide is nanoflowers.

[0008] The present invention also provides a method for preparing the PANIBi2S3 nanocomposite material, the method comprising: After mixing bismuth sulfide with chloroform, aniline is added and mixed evenly, hydrochloric acid solution and ammonium persulfate solution are added until the color of the solution changes to dark green, solid-liquid separation is performed, washing is performed, and drying is performed to obtain a nanocomposite material (PANI / Bi2S3).

[0009] Furthermore, the ratio of aniline to bismuth sulfide is 10%-30% by mass.

[0010] Furthermore, the ratio of aniline to bismuth sulfide is 20% by mass.

[0011] Furthermore, it should be understood by those skilled in the art that chloroform is mainly used to protect bismuth sulfide, and its amount is not limited. As an example, 100 mL can be added.

[0012] Furthermore, the preparation method of the ammonium persulfate solution is specifically as follows: dissolving and dispersing ammonium persulfate in deionized water.

[0013] Furthermore, the molar ratio of ammonium persulfate to aniline in the ammonium persulfate solution is 1:1.

[0014] Furthermore, the method for preparing the ammonium persulfate solution includes: dispersing ammonium persulfate in deionized water.

[0015] Furthermore, the molar concentration of the hydrochloric acid solution is 1 mol / L.

[0016] Furthermore, the preparation method of the hydrochloric acid solution includes dispersing hydrochloric acid in deionized water.

[0017] Furthermore, in terms of volume, the volume ratio of the hydrochloric acid solution to the ammonium persulfate solution is 50:12.5.

[0018] Furthermore, when adding aniline, an ice-water bath environment is used.

[0019] Furthermore, the specific method of washing includes: washing with ethanol and deionized water in sequence until the pH value of the precipitate reaches 7.

[0020] Furthermore, the drying temperature is 55°C-65°C, and the drying time is 23h-25h.

[0021] Furthermore, the preparation method of bismuth sulfide comprises: mixing ethylene glycol containing bismuth nitrate pentahydrate with ethylene glycol containing thiourea, reacting, solid-liquid separation, washing, and drying.

[0022] Furthermore, in the ethylene glycol containing bismuth nitrate pentahydrate, the molar concentration of bismuth nitrate pentahydrate is 0.5 mmol / 10 mL.

[0023] Furthermore, in the ethylene glycol containing thiourea, the mass concentration of thiourea is 3356 mg / 10 mL.

[0024] Furthermore, in order to promote uniform distribution of thiourea in ethylene glycol, thiourea is placed in ethylene glycol and then subjected to ultrasonic treatment. As an example, the ultrasonic treatment time is 15 minutes.

[0025] Furthermore, the volume ratio of the ethylene glycol containing bismuth nitrate pentahydrate to the ethylene glycol containing thiourea must be 1:1.

[0026] Furthermore, the reaction temperature is 170°C-190°C, and the reaction time is 11h-13h.

[0027] Furthermore, the specific method of washing is: washing with deionized water and ethanol at least 3 times.

[0028] Furthermore, the drying temperature is 55°C-65°C, and the drying time is 23h-25h.

[0029] The present invention also provides application of the PANIBi2S3 nanocomposite material in adsorbing iodine.

[0030] The embodiments of the present invention have the following technical effects: 1. In the nanocomposite material obtained by the present invention, firstly, polyaniline can not only improve the physical adsorption capacity of the adsorbent, but also facilitate the adsorbent to be weakly alkaline, thereby facilitating the adsorption of iodine ions; secondly, polyaniline also has high electrical conductivity, thereby facilitating charge transfer and facilitating the adsorption of iodine by bismuth sulfide; thirdly, polyaniline can also reduce the aggregation between bismuth sulfides.

[0031] 2. In the present invention, in order to improve the adsorption capacity of the composite material, the loading amount of polyaniline is further limited. When the loading amount is small, the modification of bismuth sulfide will not be significant, and its ability to adsorb iodine is limited. When the loading amount is large, the specific surface area and pore size of the composite material will be reduced, and the adsorption capacity will also be reduced. Therefore, in order to improve the adsorption capacity of the composite material in the present invention, the addition amount relationship between polyaniline and bismuth sulfide is further limited. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 : is a SEM image provided by the embodiments of the present invention and the comparative examples, wherein Figure 1 a is the SEM picture of comparative example 2. Figure 1 b is the SEM picture of comparative example 2. Figure 1 Figure c is a SEM image of Example 1 at a low magnification. Figure 1 Figure d is a SEM image of Example 1 at a high magnification. Figure 1 Figure e is the SEM image of Example 1. Figure 1 e1 is the distribution diagram of Bi element in Example 1, Figure 1 e2 is the S element distribution diagram in Example 1, Figure 1 e3 is the C element distribution diagram in Example 1, Figure 1 e4 is the N element distribution diagram in Example 1, Figure 1 Figure f is a TEM image of Example 1. Figure 1 Figure g is a TEM image of Example 1. Figure 1 h is the HRTEM image of Example 1, Figure 1 Where i is the SAED pattern of Example 1.

[0034] Figure 2 : is a test result diagram of the embodiment and the comparative example, wherein Figure 2 a is the XRD diagram of comparative example 1 and comparative example 2, Figure 2 b is the XRD diagram of Example 1 to Example 3, Figure 2 c is the FT-IR spectra of Examples 1 to 3, Figure 2 d in the figure is the Raman spectra of Example 1 to Example 3, Figure 2 e is the XPS measurement spectrum of Example 1, Figure 2f is the Bi4f XPS measurement spectrum in Example 1, Figure 2 g is the S 2p XPS measurement spectrum in Example 1, Figure 2 h is the C 1s XPS measurement spectrum in Example 1, Figure 2 Where i is the N 1s XPS measurement spectrum in Example 1.

[0035] Figure 3 are the test results of the embodiments and comparative examples, wherein Figure 3 a is the nitrogen adsorption-desorption isotherm of the embodiment and the comparative example, Figure 3 b is the pore size distribution curve of the embodiment and the comparative example.

[0036] Figure 4 are the test results of the embodiments and comparative examples, wherein Figure 4 a is the adsorption kinetic test result of gaseous iodine in the embodiment and the comparative example at 77°C, Figure 4 The sample after iodine adsorption in Example b is shown in FIG. Figure 4 c is the isothermal adsorption test results of the embodiment and the comparative example, Figure 4 d in the figure is the fitting curve of the adsorption kinetic model. Figure 4 Where e is the adsorption capacity of Example 1 at different temperatures, Figure 4 Fig. f is the absorption spectrum of Example 1. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0038] In a first aspect, some embodiments of the present invention provide a PANI Bi2S3 nanocomposite material, wherein the composite material is polyaniline (PANI) coated with bismuth sulfide (Bi2S3).

[0039] In some embodiments, the morphology of the bismuth sulfide is nanoflowers.

[0040] In a second aspect, some embodiments of the present invention also provide a method for preparing the PANI Bi2S3 nanocomposite material, the preparation method comprising: After mixing bismuth sulfide with chloroform, aniline is added and mixed evenly, hydrochloric acid and ammonium persulfate solution are added until the color of the solution changes to dark green, solid-liquid separation is performed, washing is performed, and drying is performed to obtain a nanocomposite material (PANI / Bi2S3).

[0041] In some embodiments, the ratio of aniline to bismuth sulfide is 10%-30% by mass.

[0042] In the present invention, when the loading amount of polyaniline is too small, the modification of bismuth sulfide will not be significant, and its ability to adsorb iodine is limited. When the loading amount is too large, the specific surface area and pore size of the composite material will be reduced, and the adsorption capacity will also be reduced. Therefore, in order to improve the adsorption capacity of the composite material, the addition amount relationship between aniline and bismuth sulfide is further limited to 10%-30% in the present invention.

[0043] In some embodiments, the ratio of aniline to bismuth sulfide is 20% by mass.

[0044] When the mass ratio of aniline to bismuth sulfide is 20%, the obtained adsorbent has better adsorption effect.

[0045] In some embodiments, the preparation method of the ammonium persulfate solution is specifically: dissolving and dispersing ammonium persulfate in deionized water.

[0046] In some embodiments, the molar ratio of ammonium persulfate to aniline in the ammonium persulfate solution is 1:1.

[0047] In some embodiments, the method for preparing the ammonium persulfate solution includes: dispersing ammonium persulfate in deionized water.

[0048] In some embodiments, the molar concentration of the hydrochloric acid solution is 1 mol / L.

[0049] In some embodiments, the method for preparing the hydrochloric acid solution includes dispersing hydrochloric acid in deionized water.

[0050] In some embodiments, the volume ratio of the hydrochloric acid solution to the ammonium persulfate solution is 50:12.5.

[0051] In some embodiments, when adding aniline, an ice-water bath environment is used.

[0052] In some embodiments, the specific method of washing includes: washing with ethanol and deionized water in sequence until the pH value of the precipitate reaches 7.

[0053] In some embodiments, the drying temperature is 55° C.-65° C., and the drying time is 23 h-25 h.

[0054] In some embodiments, the method for preparing bismuth sulfide includes: mixing ethylene glycol containing bismuth nitrate pentahydrate with ethylene glycol containing thiourea, reacting, separating the solid from the liquid, washing, and drying.

[0055] In some embodiments, the molar concentration of bismuth nitrate pentahydrate in the ethylene glycol containing bismuth nitrate pentahydrate is 0.5 mmol / 10 mL.

[0056] In some embodiments, the mass concentration of thiourea in the ethylene glycol containing thiourea is 3356 mg / 10 mL.

[0057] In some embodiments, in order to promote uniform distribution of thiourea in ethylene glycol, thiourea is placed in ethylene glycol and then subjected to ultrasonic treatment. As an example, the ultrasonic treatment time is 15 minutes.

[0058] In some embodiments, the volume ratio of the ethylene glycol containing bismuth nitrate pentahydrate to the ethylene glycol containing thiourea is 1:1.

[0059] In some embodiments, the reaction temperature is 170° C.-190° C., and the reaction time is 11 h-13 h.

[0060] In some embodiments, the specific method of washing is: washing with deionized water and ethanol at least 3 times.

[0061] In some embodiments, the drying temperature is 55° C.-65° C., and the drying time is 23 h-25 h.

[0062] In a third aspect, some embodiments of the present invention also provide the use of the PANIBi2S3 nanocomposite material in the adsorption of iodine.

[0063] The following is described in conjunction with specific embodiments and comparative examples: Embodiment 1: 242.5 mg (0.5 mmol) of bismuth nitrate pentahydrate was dissolved in 10 mL of ethylene glycol, recorded as solution A; at the same time, 335.6 mg of thiourea was added to 10 mL of ethylene glycol, and ultrasonically treated for 15 minutes, recorded as solution B. Then, the above solutions were fully mixed, reacted in an oven at 180°C for 12 hours, solid-liquid separation, and finally, washed repeatedly with water and ethanol 10 times, and dried at 60°C for 24 hours to obtain nanoflower bismuth sulfide; After fully mixing 23.5g of nanoflower bismuth sulfide with 100mL of chloroform, 2.3mL of aniline was added under ice-water bath conditions and stirred continuously for 30 minutes. Subsequently, 50ml of hydrochloric acid solution with a molar concentration of 1mol / L was added to the dispersed solution. Finally, 12.5mL of ammonium persulfate solution was added dropwise to the above solution (wherein the molar ratio of ammonium persulfate to aniline in the ammonium persulfate solution was 1:1) until the color turned dark green, and the solution was washed with ethanol and deionized water. The precipitate was filtered to pH = 7. The filtered precipitate was dried at 60°C for 24 hours and recorded as 10%-PANI / Bi2S3.

[0064] Embodiment 2: The preparation method is the same as that in Example 1, but the mass ratio of aniline to bismuth sulfide in Example 2 is 20%, and other parameters are the same as those in Example 1.

[0065] Example 3: The preparation method is the same as that of Example 1, but the mass ratio of aniline to bismuth sulfide in Example 3 is 30%, and other parameters are the same as those in Example 1.

[0066] Comparative Example 1: 242.5 mg (0.5 mmol) of bismuth nitrate pentahydrate was dissolved in 10 mL of ethylene glycol, recorded as solution A; at the same time, 335.6 mg of thiourea was added to 10 mL of ethylene glycol, and ultrasonically treated for 15 minutes, recorded as solution B. Then, the above solutions were fully mixed, reacted in an oven at 180°C for 12 hours, solid-liquid separation, and finally, washed repeatedly with water and ethanol 10 times, and dried at 60°C for 24 hours to obtain nanoflower bismuth sulfide, recorded as Bi2S3.

[0067] Comparative Example 2: Add 2.3 mL of aniline in an ice-water bath and stir continuously for 30 minutes. Then add 50 ml of 1 mol / L hydrochloric acid solution to the dispersed solution. Finally, add 12.5 mL of ammonium persulfate solution dropwise to the above solution (wherein the molar ratio of ammonium persulfate to aniline in the ammonium persulfate solution is 1:1) until the color turns dark green, and wash the solution with ethanol and deionized water. Filter the precipitate to pH = 7. Dry the filtered precipitate at 60 ° C for 24 hours and record it as PANI.

[0068] The present invention also obtains embodiments and comparative examples for testing, and the testing process is as follows: (1) Sample characteristics: The crystal structures of x%-PANI / Bi2S3 composites were characterized by X-ray diffractometer (XRD, XRD-6100, Shimadzu, Japan) with a scanning range of 5° to 70° at 40 kV and 40 mA Cu Kα radiation. To determine the elemental composition and elucidate the valence state in x%-PANI / Bi2S3, an X-ray photoelectron spectrometer (XPS, Qantera II, PHI, Japan) with a monochromatic Al Kα x-ray source was used. Fourier transform infrared spectra were obtained by a Fourier transform infrared spectrometer (FTIR, iS5, Nicolet, USA). The morphology and elemental distribution of PANI, Bi2S3 and x%-PANI / Bi2S3 samples were characterized using a field emission scanning electron microscope (SEM, JSM-IT500HR, JEOL, Japan) equipped with an energy dispersive X-ray spectrometer (EDS). The micromorphology and crystal structure of the materials were observed by transmission scanning electron microscopy (TEM, TECNAI G2 20 LaB6, FEI, USA). The BET method was used to obtain the specific surface area using a gas adsorption analyzer (Belsorp max, MicrotracBEL, Japan) at liquid nitrogen temperature (77K). Thermogravimetric analysis (TGA) of the materials was performed on a thermogravimetric analyzer (TGA, TGA55, TA, USA). The concentration of iodine was determined by a UV-visible spectrophotometer (UV-3600, Shimadzu, Japan).

[0069] (2) Iodine vapor adsorption: Since the scientific isotopes of the element iodine have the same electron configuration and the same potential energy surface, and they generally exhibit almost the same chemical properties, stable non-radioactive iodine is used instead of radioactive iodine to determine the iodine trapping ability of the material in iodine vapor and iodine / cyclohexane solution. In a typical experimental procedure, an excess of iodine solid is placed in an open glass Pyrex beaker, and then 20 mg of the adsorbent is placed in an airtight container, which is finally sealed with a lid. The glass flask is heated in an oven at 350K and 1 bar, and after capturing iodine vapor for a period of time, the container is cooled to room temperature and weighed. The amount of iodine adsorbed Q (wt%) is calculated based on the change in the weighed mass, and the calculation equation is as follows: ; Where m1 and m2 represent the mass (mg) of x%-PANI / Bi2S3 composite material before and after iodine vapor adsorption, respectively.

[0070] (3) Adsorption of iodine in liquid phase: The adsorption performance of x%-PANI / Bi2S3 nanocomposites for iodine in solution was evaluated using iodine / cyclohexane solution. 20 mg of x%-PANI / Bi2S3 sample was dispersed in 20 mL of iodine / cyclohexane solution, and the residual iodine content in the solution was measured at certain time points. The iodine concentration in the supernatant was measured using a UV-Vis spectrophotometer. The equilibrium adsorption capacity (Q e , mg / g) is calculated by the following equation: ; Where C0 and C e Respectively represent the iodine concentration before and after adsorption (mg / L); V represents the volume of iodine / cyclohexane solution (L); m represents the mass of the PANI / Bi2S3 sample used (mg).

[0071] Results and Analysis: Table 1 Specific surface area, average pore diameter and pore volume of examples and comparative examples

[0072] Table 2 Comparison between the embodiments of the present invention and the prior art

[0073] Table 3 Parameters of fitting pseudo first-order kinetic model and pseudo second-order kinetic model

[0074] Table 4 Thermodynamic parameters of iodine adsorption in the examples

[0075] The microstructure and morphology of the obtained product were observed by SEM. Figure 1 As shown in (a), the formed PANI exhibits a typical rod-like structure with an average diameter of 50 nm; Figure 1 As shown in (b), the SEM image of Bi2S3 shows a hierarchical nanoflower structure with a smooth surface and good crystallinity, consisting of many interconnected nanorods with an average diameter of 3 μm. Figure 1 (c)- Figure 1 (d) shows the low-magnification SEM image and high-magnification SEM image of 10%-PANI / Bi2S3. The composite material inherits the hierarchical nanoflower structure of Bi2S3, and its surface is covered by PANI. Figure 1 (e) and Figure 1 (e1)- Figure 1 The elemental mapping in (e4) shows that element C and element N are uniformly dispersed on the surface of Bi2S3 nanoflowers, confirming the successful synthesis of PANI / Bi2S3 materials.

[0076] In order to further reveal the microstructure of the prepared product, PANI / Bi2S3 nanomaterials were analyzed by TEM and HRTEM. Figure 1 (f)- Figure 1 TEM in (g) shows that PANI is loaded on the surface of Bi2S3 nanoflowers and the PANI / Bi2S3 composite material grows in the form of nanoflowers, which is consistent with the SEM results. Figure 1 (h) shows the HRTEM image of PANI / Bi2S3. PANI / Bi2S3 corresponds to a (220) interplanar spacing of 0.391 nm, which matches the (220) plane of Bi2S3. Figure 1 (i) shows the selected area electron diffraction (SAED) pattern, confirming the polycrystalline nature of the material.

[0077] The structures of Bi2S3, PANI and PANI / Bi2S3 were confirmed by X-ray diffraction (XRD). Figure 2 As shown in (a), the typical diffraction peaks of PANI appear at 2θ=21.1° and 25.6°, which belong to the (020) crystal plane and (200) crystal plane diffraction of polyaniline adamantane-adamantaldehyde salt (ES), respectively. In the XRD pattern of synthesized Bi2S3, the peaks at 2θ=15.9°, 17.8°, 22.6°, 23.9°, 25.1°, 28.8°, 32.0°, 33.1°, 35.8°, 40.1°, 42.8°, 45.7°, 46.7°, 49.3°, 52.9°, 59.4°, 62.8°, 65.3°, 67.9° and 69.6° are respectively related to the (200) crystal plane, (120) crystal plane and (120) crystal plane. The lattice planes of the synthesized PANI / Bi2S3 are consistent, (JCPDS NO.17-0320). Figure 2 As shown in (b), it has diffraction peaks of Bi2S3 and PANI, which confirms the successful preparation of PANI / Bi2S3 material in the present invention.

[0078] To further verify the chemical bonding and vibration bands of PANI / Bi2S3 nanomaterials, FTIR vibrational spectroscopy was performed. Figure 2 (c) 795cm -1 、948cm -1 、1297cm -1 、1475cm-1 and 1588cm -1 The absorption peaks at 3 correspond to the CH bonding mode of the aromatic ring, the NH + 1109cm -1 and 1375cm -1 The peak at belongs to the stretching vibration of the Bi-S bond in Bi2S3, which further proves the successful preparation of the composite material.

[0079] The PANI / Bi2S3 heterostructures were further characterized by Raman spectroscopy, e.g. Figure 2 (d) The Raman spectrum obtained at 128 cm -1 、437cm -1 and 965cm -1 The characteristic peaks at 1162 cm -1 、1379cm -1 、1497cm -1 and 1579cm -1 The peaks at are characteristic peaks of PANI, which are attributed to the bending vibration of the quinone ring CH of PANI, the stretching vibration of the aromatic amine Ar-N, the stretching vibration of C=N, and the stretching vibration of C=C. The quinone and hydroquinone structures of PANI show redox activity, which can accept and release electrons, thus promoting electron transfer between materials, which is beneficial to improving the adsorption capacity of Bi2S3 for iodide ions.

[0080] In addition, XPS analysis was further explored to determine the surface composition and chemical state of elements in PANI / Bi2S3 nanomaterials. Figure 2 (e) The spectral study shows that, taking 10%-PANI / Bi2S3 as an example, 10%-PANI / Bi2S3 involves C, N, S and Bi elements. Figure 2 In (f), the two strong peaks at 160 eV and 165.3 eV are attributed to Bi 4f 7 / 2 and Bi4f 5 / 2 , which is due to the formation of Bi2S3; in addition, the Bi 4f spectrum also contains another group of weak peaks (158.9eV and 164.3eV, corresponding to Bi 4f 7 / 2 and Bi 4f 5 / 2 ), which confirms the coexistence of two different chemical allotropes of bismuth. Figure 2 As shown in (g), the peaks at 164.1 eV and 165.3 eV are attributed to S 2p 3 / 2 and S 2p 5 / 2.exist Figure 2 The high-resolution C 1s spectrum at 284.8 eV, 285.9 eV, and 287.7 eV in (h) can be decomposed into three peaks, which are attributed to CC, CO, and C=O bonds, respectively. Figure 2 In the high-resolution spectrum of N 1s in (i), two peaks with binding energies of 399.9 eV and 400.7 eV are associated with different nitrogen forms corresponding to pyridinic-N (=N-) and pyrrolic-N (-NH-). The above results further demonstrate the successful synthesis of PANI / Bi2S3 composites.

[0081] like Figure 3 As shown in (a), the specific surface area and pore structure of the materials were analyzed using nitrogen adsorption-desorption isotherms. All samples showed a hysteresis loop of type H3, which is related to the typical type IV adsorption isotherm characteristics of mesoporous materials, indicating that they have a typical mesoporous structure. The corresponding pore size distribution analysis further verified this conclusion, such as Figure 3 As shown in (b), the specific surface area of ​​the composite material increases significantly with the increase of PANI. Compared with Bi2S3, the pore volume of the embodiment of the present invention also increases to 0.142 cm 3 / g, 0.164cm 3 / g and 0.134cm 3 / g (Table 1). The increase in surface area and pore volume of PANI / Bi2S3 composites can provide more adsorption sites and space for reactant molecules.

[0082] There are a large number of free amino groups (-N) and π-π conjugated structures in PANI, which can provide a large number of active sites and good adsorption effects on iodine. In Bi2S3, there is a Bi-S bond with lower electronegativity, which is easier to break and form a new chemical bond with iodine. Therefore, PANI / Bi2S3 composite materials may be potential effective materials for radioactive iodine capture. The iodine capture ability was tested by placing the material in iodine vapor at 75°C and ambient pressure. Figure 4 (a)- Figure 4As shown in (b), the iodine absorption capacity of the samples at different time intervals was determined by the gravimetric method. All samples showed a rapid iodine absorption rate within the first 10 minutes and remained unchanged after 4.5 hours, indicating that adsorption equilibrium had been reached. Since the loading amounts of PANI were 10%, 20% and 30%, respectively, the iodine uptake of the PANI / Bi2S3 composite material increased to 321.0wt%, 330.7wt% and 291.3wt% after 4.5 hours, respectively, which was significantly higher than PANI (93.9wt%) and Bi2S3 (140.6wt%). This may be due to the increase in the specific surface area and pore volume of the composite material caused by the PANI loading, thereby providing more active sites for iodine. At the same time, PANI has high conductivity and can directly promote the capture of iodine by Bi2S3 by transferring electrons; in addition, the interaction between the embodiment obtained in the present invention and iodine is further enhanced because PANI contains a large number of free amino groups.

[0083] Compared with the reported bismuth-based materials, silver-based materials, MOFs and COFs materials, the best iodine adsorption capacity of PANI / Bi2S3 nanoflowers at 77 °C (3307 mg g for 10%-PANI / Bi2S3) was -1 ) showed better adsorption performance (as shown in Table 2).

[0084] Isothermal adsorption experiments were conducted by comparing the adsorption of I2 by PANI, Bi2S3, 10%-PANI / Bi2S3, 20%-PAIN / Bi2S3, and 30%-PANI / Bi2S3 in cyclohexane solutions with different initial I2 concentrations, as shown in Figure 2. Figure 4(c) is shown. The curve shows that the iodine adsorption capacity of each adsorbent increases rapidly with the increase of the initial iodine concentration in the solution until equilibrium is reached. Finally, in the embodiment of the present invention, due to the PANI loading, the maximum equilibrium adsorption capacity of 10%-PANI / Bi2S3, 20%-PANI / Bi2S3 and 30%-PANI / Bi2S3 for I2 are 1235.8mg / g, 1361.3mg / g and 1110.3mg / g, respectively. The loading of PANI nanorods effectively improves the iodine adsorption performance of Bi2S3 nanoflowers, which is mainly attributed to the increase in specific surface area and pore volume, which effectively prevents the aggregation of Bi2S3 during the reaction. In addition, the saturated adsorption capacity of the composite material increases first and then decreases with the increase of PANI content. When the doping amount of PANI is 10% to 20%, the introduction of PANI leads to an increase in the active sites of the composite material, thereby increasing their adsorption capacity. When the doping amount of PANI is increased to 30%, the adsorption performance decreases due to the decrease in specific surface area and pore size. Therefore, it can be concluded that the introduction of an appropriate amount of PANI can effectively increase the active sites of the composite material, thereby further improving the adsorption performance of the material. Further preferably, the mass ratio of aniline to bismuth sulfide is 20%.

[0085] In order to better study the iodine adsorption process and the corresponding rate-controlling step, the pseudo first-order kinetic model and pseudo second-order kinetic model were used to fit the kinetic data. The formula is as follows: ; ; where q t (mg g -1 ) is the adsorption capacity at time t (min), q e (mg g -1 ) refers to the adsorption capacity at equilibrium. k1 and k2 (g mg -1 min -1 ) are the adsorption rate constants of the pseudo-first-order kinetic model and the pseudo-second-order kinetic model, respectively.

[0086] The model fitting curve and corresponding parameters are as follows Figure 4 (d) and shown in Table 3. The correlation coefficient (R) obtained using the pseudo second-order kinetic model 2 ) are higher than the pseudo-first-order kinetic model, indicating that the pseudo-second-order kinetic model is more suitable for describing the adsorption process of the composite material on I2, and the adsorption process of PANI / Bi2S3 on I2 is rate-controlled chemical adsorption.

[0087] In order to study the effect of PANI / Bi2S3 composite materials on I2 adsorption performance at different solution temperatures, 10%-PANI / Bi2S3 was taken as an example to conduct further research and test its adsorption capacity and equilibrium time at temperatures ranging from 298K to 328K. The results are shown in Figure 4 As shown in (e), with the increase of solution temperature, the adsorption capacity of 10%-PANI / Bi2S3 for I2 increased from 1228.4 mg g to -1 Increased to 1301.1 mg g -1 This indicates that the adsorption of iodine monomer by the composite material is an endothermic process. In order to further understand the change of internal energy during the adsorption process, the thermodynamic parameters (△G 0 , △H 0 , △S 0 ), as shown in the following formula:

[0088]

[0089] Where △G 0 (kJ·mol -1 ), △H 0 (kJ.mol -1 ) and △S 0 (J.mol -1 ·K -1 ) are Gibbs free energy, enthalpy and entropy change, respectively; K is the thermodynamic equilibrium constant; R (8.314 J mol -1 K -1 ) is the universal gas constant; T(K) is the solution temperature. A linear plot of 1 / T was plotted against lnK to obtain the slope and intercept, and the calculated thermodynamic parameters are shown in Table 4. At solution temperatures of 298K, 308K, and 318K, △G 0 The value <0 indicates that the adsorption process of the composite on I2 is spontaneous. 0 >0 means that heat is absorbed during the adsorption process, indicating that the increase in temperature promotes the adsorption of radioactive iodine. 0 >0 indicates that the internal degree of freedom of the system increases as the adsorption process proceeds. This further verifies that the adsorption of iodine monomer by the composite material is an exothermic process.

[0090] In addition, we found that the adsorption of I2 by the PANI / Bi2S3 composite material is reversible. To this end, 10%-PANI / Bi2S3 was used as an example to adsorb iodine. 5 mg of the sample after iodine adsorption was taken and 5 mg of 10%-PANI / Bi2S3-I was added to 10 ml of ethanol solution. The absorption spectrum of the composite material at different time intervals in the ethanol solution was studied by UV-visible spectroscopy to study its release process. Figure 4 As shown in (f), the spectrum shows characteristic peaks at 288 nm and 360 nm, which are attributed to I3 - and I5 - This also indicates that Bi2S3 and I2 undergo a chemical reaction to form polyiodide ions.

[0091] In summary, the results of this study indicate that PANI / Bi2S3 nanocomposites can effectively remove radioactive iodine. Compared with pure Bi2S3 nanoflowers, the iodine uptake capacity and equilibrium rate of PANI / Bi2S3 composites were significantly improved. This can be attributed to the fact that PANI contains a large number of nitrogen-containing groups with high affinity for soft Lewis acidic I2, which facilitates the uptake of a large amount of I2. At the same time, PANI has high conductivity, which can further promote iodine capture via electron transfer. The synthesized PANI / Bi2S3 composite has high iodine uptake capacities of up to 330.7wt% and 1361.3mg g for radioactive iodine in the gas and liquid phases, respectively. -1 In summary, the excellent iodine absorption capacity of PANI / Bi2S3 indicates that it has great application potential in iodine absorption.

[0092] It should be noted that the terms used in the present invention are only for describing specific embodiments, rather than limiting the scope of the present application. As shown in the present specification, unless the context clearly indicates an exception, the words "one", "a", "a kind of" and / or "the" do not specifically refer to the singular, but may also include the plural. The terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method or device. In the absence of more restrictions, the elements defined by the sentence "include one..." do not exclude the presence of other identical elements in the process, method or device including the elements.

[0093] It should also be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. Unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", etc. should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.

[0095] References: [1]Y. Nan, LL Tavlarides, DW DePaoli, Adsorption of iodine onhydrogen‐reduced silver‐exchanged mordenite: Experiments and modeling, AIChEJournal 63 (2017). [2]Y. Tan, R. Wang, Q. Zhao, T. Duan, L. Zhu, One-step synthesis ofAg@polyaniline core–shell particles for efficient removal of radioactiveiodine, J Radioanal Nucl Chem 333 (2024) 2105–2114. https: / / doi.org / 10.1007 / s10967-024-09444-3. [3]X. Wang, M. Li, J. Zhang, X. He, J.C. Crittenden, W. Zhang, SilverIon-Exchanged Anionic Metal–Organic Frameworks for Iodine Adsorption: SilverSpecies Evolution from Ions to Nanoparticles, ACS Appl. Nano Mater. 6 (2023)7206–7217. https: / / doi.org / 10.1021 / acsanm.3c00264. [4]T. Assaad, B. Assfour, Metal organic framework MIL-101 forradioiodine capture and storage, Journal of Nuclear Materials 493 (2017) 6–11. https: / / doi.org / 10.1016 / j.jnucmat.2017.05.036. [5]C. Wang, H. Yao, J. Sun, T. Tong, Z. Ye, H. Dong, C. Li, S. Ma,Nanoscale assembly of MoS2 / CoS2 / Ni3S2 grown on Ni foam for synergisticcapture of iodine, Chemical Engineering Journal 493 (2024) 152514. https: / / doi.org / 10.1016 / j.cej.2024.152514. [6]L. Zhang, M. Li, X. Liu, J. Feng, Y. Liu, Y. Tu, S. Li, T. Duan,Fabrication of amidoxime grafted polyacrylonitrile for iodine vapor capturefrom off-gas, Chemical Engineering Journal 493 (2024) 152618. https: / / doi.org / 10.1016 / j.cej.2024.152618. [7]Y. Xiong, Y. Ai, H. Wang, Y. Zhang, X. He, H. Dan, Y. Ding, Facilesynthesis of novel Cu0@SiO2 adsorbents derived from rice husk for highlyefficient capture iodine gas, J Sol-Gel Sci Technol 107 (2023) 503–511.https: / / doi.org / 10.1007 / s10971-023-06100-2. [8]M.M. Khan, K.-W. Chen, Y.-T. Chen, H.-Y. Liu, M. Xia, F. Ni, C.-H.Gong, P. Wang, Y. Yang, A highly efficient composite of Cu-BTC and g-C3N4with bismuth doped for the adsorption of radioactive iodine, Separation andPurification Technology 354 (2025) 128746. https: / / doi.org / 10.1016 / j.seppur.2024.128746. [9]M.A.S. Salem, A.M. Khan, Y.K. Manea, M.T.A. Qashqoosh, F.A.M.Alahdal, Highly efficient iodine capture and ultrafast fluorescent detectionof heavy metals using PANI / LDH@CNT nanocomposite, Journal of HazardousMaterials 447 (2023) 130732. https: / / doi.org / 10.1016 / j.jhazmat.2023.130732.

[10] K. Chen, A. Gu, X. Zhou, P. Wang, C. Gong, P. Mao, Y. Jiao, K.Chen, Y. Yang, In-situ growth of zeolitic imidazolate framework-8 onpolypyrrole nanotubes for highly efficient and reversible capture ofradioiodine, Colloids and Surfaces A: Physicochemical and Engineering Aspects658 (2023) 130751. https: / / doi.org / 10.1016 / j.colsurfa.2022.130751.

[11] K. Chen, P. Wang, A. Gu, E. Djam Miensah, C. Gong, P. Mao, Y.Jiao, K. Chen, Y. Liu, Y. Yang, Core-shell Bi2S3 nanorods loaded ZIF-8nanocomposites for efficient and reversible capture of radioactive iodine,Microporous and Mesoporous Materials 339 (2022) 111983. https: / / doi.org / 10.1016 / j.micromeso.2022.111983.

Claims

1. A PANI Bi2S3 nanocomposite material, characterized in that: The composite material is polyaniline-coated bismuth sulfide.

2. The nanocomposite material according to claim 1, characterized in that The morphology of the bismuth sulfide is nanoflower.

3. The method for preparing the PANI Bi2S3 nanocomposite material according to any one of claims 1 to 2, characterized in that: The preparation method comprises: After mixing bismuth sulfide and chloroform, aniline is added, mixed evenly, hydrochloric acid and ammonium persulfate solution are added until the solution changes to dark green, solid-liquid separation is performed, washing is performed, and drying is performed to obtain a nanocomposite material.

4. The preparation method according to claim 3, characterized in that: The ratio of aniline to bismuth sulfide is 10%-30% by mass.

5. The preparation method according to claim 3, characterized in that: The molar ratio of ammonium persulfate to aniline in the ammonium persulfate solution is 1:1; The molar concentration of the hydrochloric acid solution is 1 mol / L.

6. The preparation method according to claim 3, characterized in that: In terms of volume, the volume ratio of the hydrochloric acid solution to the ammonium persulfate solution is 50:12.

5.

7. The preparation method according to claim 3, characterized in that: When adding aniline, an ice-water bath environment condition is adopted.

8. The preparation method according to claim 3, characterized in that: The specific method of washing includes: washing with ethanol and deionized water in sequence until the p value of the precipitate is 7.

9. The preparation method according to claim 3, characterized in that: The drying temperature is 55° C.-65° C., and the drying time is 23 h-25 h.

10. Use of the PANIBi2S3 nanocomposite material according to any one of claims 1 to 2 or the PANIBi2S3 nanocomposite material obtained by the preparation method according to any one of claims 3 to 9 in adsorbing iodine.

Citation Information

Patent Citations

  • Bismuth sulfide / carbon nanotube composite material, and preparation method and application thereof

    CN106252661A

  • Bamboo-leaf-shaped bismuth sulfide nanosheet catalytic material, and preparation method and application thereof

    CN111185196A

  • Bismuth sulfide nanorod / bismuth oxybromide composite photocatalytic material, preparation method and application of bismuth sulfide nanorod / bismuth oxybromide composite photocatalytic material in removal of organic pollutants in wastewater

    CN117732488A